Value and Limitations of Broad Brush Surveys Used in Community-Randomized Trials in Southern Africa. (April 2019) - Bond, Virginia; Ngwenya, Fredrick; Murray, Emma; Ngwenya, Nothando; Viljoen, Lario; Gumede, Dumile; Bwalya, Chiti; Mantantana, Jabulile; Hoddinott, Graeme; Dodd, Peter J.; Ayles, Helen; Simwinga, Musonda; et al.
We describe and reflect on a rapid qualitative survey approach called "Broad Brush Survey" (BBS) used in six community-randomized trials (CRTs)/studies in Zambia and South Africa (2004–2018) to document, compare, classify, and communicate community features systematically for public health and multidisciplinary research ends. BBS is based on a set sequence of participatory qualitative methods and fieldwork carried out prior to a CRT intervention and/or research by social scientists to generate rapid community profiles using four key indicators: physical features, social organization, networks, and community narratives. Profiling makes apparent similarities and differences, enabling comparison across communities and can be facilitated by an ideal model of open-closed systems. Findings have provided practical outputs (e.g., community profiles) and academic opportunities (e.g., community typologies). The BBS approach enables complex social landscapes to be incorporated in CRTs. This method has proven to be useful, adaptable and to have multidisciplinary appeal.